Brassica rapa L. subsp. rapa NGB 13847 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Brassica rapa L. subsp. rapa Common name(s): BrassicaComplex, Brassica complex Other names: Gibostad Stamme Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 13847 Method of creation: Acquisition Date: 1999-01-01 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...